Cash Dividend Policy Analysis in The Property Industry Listed on IDX - Yuliana Yuliana; Naning Putri Utami (President University, 2022)
The purpose of this study is to examine the relationship between the current ratio, debt-to-asset ratio, return on asset ratio, firm size, and asset growth and the dividend payout ratio in the property, real estate, and building construction industry as represented by the Indonesia Stock Exchange (IDX) from 2016 to 2018. The research population was comprised of all property, immobilier and building subsectors traded publicly at the Indonesian Stock Exchange (IDX) between 2016 and 2018, with a total of 51 companies. Gather data from the 14 firms featured in the research has been employed with purposive sampling. Data from the IDX annual report were received, which can be accessed at www.IDX.co.id. In this research, a regression of panel data was used to analyze the data. The current ratio, asset return and company size appear to have no significant influence on decisions on cash dividends. Only the debt-to-asset ratio and asset growth have an important impact on decisions concerning cash dividends